Reconstruction of a meteotsunami in Lake Erie on 27 May 2012: Roles of atmospheric conditions on hydrodynamic response in enclosed basins. Issue 12 (18th December 2015) - Anderson, Eric J.; Bechle, Adam J.; Wu, Chin H.; Schwab, David J.; Mann, Greg E.; Lombardy, Kirk A.
Abstract: On 27 May 2012, atmospheric conditions gave rise to two convective systems that generated a series of waves in the meteotsunami band on Lake Erie. The resulting waves swept three swimmers a 0.5 mi offshore, inundated a marina, and may have led to a capsized boat along the southern shoreline. Analysis of radial velocities from a nearby radar tower in combination with coastal meteorological observation indicates that the convective systems produced a series of outflow bands that were the likely atmospheric cause of the meteotsunami. In order to explain the processes that led to meteotsunami generation, we model the hydrodynamic response to three meteorological forcing scenarios: (i) the reconstructed atmospheric disturbance from radar analysis, (ii) simulated conditions from a high‐resolution weather model, and (iii) interpolated meteorological conditions from the NOAA Great Lakes Coastal Forecasting System. The results reveal that the convective systems generated a series of waves incident to the southern shore of the lake that reflected toward the northern shoreline and reflected again to the southern shore, resulting in spatial wave focusing and edge wave formation that combined to impact recreational users near Cleveland, OH. This study illustrates the effects of meteotsunami development in an enclosed basin, including wave reflection, focusing, and edge wave formation as well as temporal lags between the causative atmospheric conditions and arrival of dangerous wave conditions. As a result, the ability to detect these extreme storms and predict the hydrodynamic response is crucial to reducing risk and building resilient coastal communities. Key Points: Radar‐based velocity allows for detection of meteotsunami‐inducing front Wave reflection, focusing, and edge waves led to meteotsunami conditions Enclosed basins can induce temporal lags between storm front and wave response